PENGARUH PERCEIVED USEFULNESS, PERCEIVED EASE OF USED DAN TRUST TERHADAP REPURCHASE INTENTION PENGGUNA LAYANAN E-COMMERCE - Anthapratama, Fahrezi Ihza; Rohman, Fatchur (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The objective of this research is to identify the effect of perceived usefulness, perceived ease of use and trust on the repurchase intention of Tokopedia users in Malang city. This study is categorized as explanatory research, which explains the causal relationship between variables through hypothesis testing. From the population of Tokopedia users in Malang city, 100 people were selected as the research respondents through purposive sampling technique. The data was analyzed using statistical descriptive analysis and multiple linear regression in SPSS 26. This study finds that perceived usefulness and trust significantly influence the repurchase intention and that perceived ease of use does not significantly affect the repurchase intention of Tokopedia users in Malang city.